Ultrastructural features, chromium content and in situ immunodetection of 5-methyl-cytosine following Cr (VI) treatment in two strains of Scenedesmus acutus M. (Chlorophyceae) with different chromium sensitivity. Issue 3 (2nd July 2016) - Cozza, Davide; Torelli, Anna; Veltri, Alessandra; Ferrari, Michele; Marieschi, Matteo; Cozza, Radiana
Abstract: Two strains of the unicellular green alga Scenedesmus acutus (F.J.F. Meyen) with different sensitivity to chromium (VI) were compared to evaluate their ultrastructural morphology in chromium-free and -supplemented medium with a sub-lethal concentration of Cr(VI) for 72 hours. The ultrastructural alteration in different cytological compartments indicated that Cr(VI) induced earlier and stronger alterations in the wild type (wt) compared with the chromium-tolerant strain (Cr-t). After Cr treatments, ICP-MS (Inductively Coupled Plasma Mass Spectrometry) showed a higher Cr accumulation in the wild type than in the Cr-tolerant strain, suggesting a more efficient chromium-exclusion mechanism in the latter. The Cr treatment induced an increase in the nuclear area and a rearrangement in the eu-heterochromatic fraction, suggesting that chromatin remodelling could be at the basis of differential gene expression and metal tolerance. To gain additional information on the remodelling of the nuclear chromatin, we analysed DNA methylation by immunolocalization of 5-methyl-cytosine, before and after Cr exposure. Significant differences in the quantification of the immunolabelling of DNA cytosine-rich zones between the two strains were observed. These data suggest that an epigenetic mechanism could be at the basis of the Cr tolerance in S. acutus, as supported by previous data reporting that the acquired tolerance was inherited and maintained through the progeny.